Transparent heat management film based on electrostatic deposition of micro-nano scattering layer and preparation method thereof
Patent Information
- Application Number
- CN202610722212.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-25
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-05-25
AI Technical Summary
[0005]本发明的目的在于提供一种基于静电沉积微纳散射层的透明热管理膜及其制备方法,以解决现有技术中透明性与近红外阻隔性能难以兼顾、近红外辐射调控机制单一以及金属镀层工艺复杂、设备成本高、对基材适配性受限等技术问题
[0026](1)光谱协同:本发明采用透明复合基体层与静电沉积微纳散射层相结合的双层结构设计,其中透明复合基体层中的近红外屏蔽颗粒对近红外辐射进行前级吸收,静电沉积微纳散射层对剩余近红外辐射进行后级散射和反射,从而实现对近红外辐射的协同调控,有利于在保持较高可见光透过率的同时降低近红外透过率。
Smart Images

Figure CN122253511B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of transparent functional films and thermal management technology, and specifically relates to a transparent thermal management film based on electrostatically deposited micro-nano scattering layers and its preparation method. Background Technology
[0002] With the continuous improvement of building energy conservation, automotive thermal management, and the functionalization of transparent building envelopes, the ability of transparent materials to regulate solar radiation heat input is receiving increasing attention, in addition to meeting the requirements of lighting and visibility. In the solar spectrum, the visible light band mainly affects the lighting performance of transparent components, while the near-infrared band carries approximately 52% of solar radiation energy. Near-infrared radiation, after passing through transparent components and entering indoor or vehicle interiors, easily causes heat accumulation, thereby increasing the load on air conditioning systems and energy consumption. Therefore, developing transparent thermal management materials with both high visible light transmittance and low near-infrared transmittance has significant application value.
[0003] Existing transparent thermal management technologies mainly include the following approaches: metal coatings or sputtered coatings primarily rely on the reflection or absorption of near-infrared radiation by the metal layer to achieve thermal management, but they typically suffer from complex processes, high equipment costs, limited substrate compatibility, and difficulties in continuous fabrication; low-emissivity coated glass mainly achieves thermal management by reducing long-wave heat radiation transmission, but its ability to control the transmission of near-infrared solar radiation remains insufficient; transparent thermal insulation materials mostly focus on reducing heat conduction or rely on a single near-infrared absorption mechanism, with limited ability to synergistically manage solar radiation, especially in the near-infrared band, and often struggle to further reduce near-infrared transmittance while maintaining high visible light transmittance. Furthermore, existing technologies for controlling near-infrared radiation mostly rely on a single mechanism, lacking structural designs for graded attenuation and synergistic control of near-infrared radiation, thus making it difficult to achieve a good balance between transparency, near-infrared blocking capability, process simplicity, and application adaptability.
[0004] Therefore, there is an urgent need to provide a new transparent thermal management film and its preparation method to solve the technical problems in the existing technology, such as the difficulty in achieving both transparency and near-infrared blocking performance, the single near-infrared radiation regulation mechanism, and the complexity of metal coating processes. Summary of the Invention
[0005] The purpose of this invention is to provide a transparent thermal management film based on an electrostatically deposited micro / nano scattering layer and its preparation method, in order to solve the technical problems in the prior art, such as the difficulty in achieving both transparency and near-infrared blocking performance, the single near-infrared radiation regulation mechanism, and the complexity of metal coating processes, high equipment costs, and limited adaptability to substrates.
[0006] To achieve the above objectives, the present invention provides a transparent thermal management film based on an electrostatically deposited micro / nano scattering layer, comprising a transparent composite substrate layer and an electrostatically deposited micro / nano scattering layer disposed on the back surface of the transparent composite substrate layer; wherein, the transparent composite substrate layer is composed of a transparent polymer matrix and near-infrared shielding particles dispersed in the transparent polymer matrix; and the electrostatically deposited micro / nano scattering layer is a micro / nano particle layer or a micro / nano fiber layer formed by electrostatic deposition.
[0007] The transparent polymer matrix described in this invention provides film-forming properties, transparency, and mechanical support for the membrane; the near-infrared shielding particles selectively absorb or shield incident near-infrared radiation to form a pre-stage modulation of near-infrared radiation; the electrostatically deposited micro / nano scattering layer scatters and reflects the remaining near-infrared radiation transmitted through the transparent composite matrix layer to form a post-stage modulation of near-infrared radiation, thereby reducing the near-infrared transmittance of the transparent thermal management film through the synergistic effect of pre-stage absorption and post-stage scattering / reflection.
[0008] Preferably, the transparent polymer matrix includes, but is not limited to, one or more of polydimethylsiloxane, polymethyl methacrylate, polyurethane, polycarbonate, polyvinyl alcohol, and epoxy resin.
[0009] Preferably, the near-infrared shielding particles are inorganic particles with near-infrared absorption, shielding or modulation functions, including but not limited to one or more of indium tin oxide, antimony-doped tin oxide, cesium tungsten oxide, zinc oxide, and tungsten oxide.
[0010] Preferably, the electrostatically deposited micro / nano scattering layer is a layer of micron- and / or nano-sized particles formed by electrostatic spraying, or a layer of micron- and / or nano-sized fibers formed by electrospinning.
[0011] More preferably, the electrostatically deposited micro / nano scattering layer is a discretely distributed layer of micron- and / or nano-sized particles.
[0012] Furthermore, the electrostatically deposited micro / nano scattering layer is a continuous layer, a semi-continuous layer, or a discretely distributed layer.
[0013] Preferably, the electrostatically deposited micro / nano scattering layer is formed of a polymer material, or is formed of a polymer material combined with functional particles.
[0014] Furthermore, the polymer material is a polymer material that can be electrostatically deposited, including but not limited to one or more of polyurethane, polyamide, polyvinylidene fluoride, polyacrylonitrile, and polyvinyl alcohol; the functional particles are inorganic particles with spectral modulation function, including but not limited to one or more of indium tin oxide, antimony-doped tin oxide, titanium dioxide, silicon dioxide, and aluminum oxide.
[0015] The present invention also provides a method for preparing the above-mentioned transparent thermal management film based on an electrostatically deposited micro / nano scattering layer, comprising the following steps:
[0016] (1) A transparent polymer matrix is provided, and near-infrared shielding particles are added thereto, and the matrix is mixed and dispersed to form a transparent composite matrix layer precursor;
[0017] (2) The transparent composite matrix layer precursor is formed into a film and then cured or shaped to obtain a transparent composite matrix layer;
[0018] (3) An electrostatically deposited micro-nano scattering layer is formed on the surface of the transparent composite substrate layer on the side opposite to the incident light direction by electrostatic deposition, thereby obtaining a transparent thermal management film.
[0019] Preferably, the near-infrared shielding particles in step (1) are dispersed in a transparent polymer matrix by one or more of the following methods: mechanical stirring, ultrasonic dispersion, ball milling dispersion, or surface modification dispersion.
[0020] Preferably, the film-forming method in step (2) is selected from one or more of solution casting, scraping, casting, spin coating, spraying, molding, hot pressing or in-situ curing.
[0021] Preferably, the electrostatic deposition method in step (3) is electrospinning or electrostatic spraying, and the morphology, coverage and thickness of the electrostatically deposited micro-nano scattering layer can be controlled by adjusting the concentration of the deposition liquid, the applied voltage, the propulsion speed, the receiving distance and the deposition time.
[0022] Furthermore, by reducing the concentration of the deposition solution, the electrostatic deposition method can be changed from fiber deposition to particle deposition to form an electrostatic spray particle layer.
[0023] The present invention also provides an application of the above-mentioned transparent thermal management film based on electrostatically deposited micro-nano scattering layer in transparent energy-saving windows, transparent automotive components, or transparent building envelopes.
[0024] Unlike existing technologies that rely on a single near-infrared absorption mechanism, a single surface scattering mechanism, or a metal coating for thermal management, this invention constructs a hierarchical synergistic structure consisting of a transparent composite substrate layer and an electrostatically deposited micro / nano scattering layer on the side facing away from the incident light. The transparent composite substrate layer maintains visible light transmission while using near-infrared shielding particles to perform pre-stage absorption of incident near-infrared radiation; the electrostatically deposited micro / nano scattering layer utilizes the size effect of the micro / nano structure to perform post-stage scattering and reflection of the remaining near-infrared radiation transmitted through the transparent composite substrate layer. Thus, this invention achieves hierarchical weakening and synergistic control of the "pre-stage absorption-post-stage reflection" of near-infrared radiation, avoiding the problems of decreased transparency due to simply increasing particle absorption or increased visible light haze due to simply enhancing surface scattering, thereby balancing high visible light transmittance and low near-infrared transmittance. Furthermore, the electrostatically deposited micro / nano scattering layer can be flexibly constructed into a fiber layer or a particle layer through electrospinning or electrospraying, giving this invention good structural adjustability and process adaptability.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] (1) Spectral synergy: The present invention adopts a double-layer structure design combining a transparent composite matrix layer and an electrostatically deposited micro-nano scattering layer. The near-infrared shielding particles in the transparent composite matrix layer perform pre-stage absorption of near-infrared radiation, and the electrostatically deposited micro-nano scattering layer performs post-stage scattering and reflection of the remaining near-infrared radiation, thereby achieving synergistic regulation of near-infrared radiation, which is beneficial to reduce near-infrared transmittance while maintaining high visible light transmittance.
[0027] (2) Simple process: This invention does not require complex processes such as metal plating or vacuum sputtering. It can be prepared by composite film formation and electrostatic deposition. It has the advantages of relatively simple process, relatively low equipment requirements, good adaptability to substrate and easy continuous preparation.
[0028] (3) Transparency and thermal management: In this invention, the transparent composite matrix layer and the electrostatically deposited micro-nano scattering layer respectively undertake the functions of near-infrared absorption and near-infrared scattering / reflection, avoiding the problem that transparency and thermal management performance are difficult to balance under a single control mechanism, which is conducive to improving the comprehensive performance of the material in the thermal management application of transparent components.
[0029] (4) Adjustable structure: The electrostatically deposited micro-nano scattering layer in this invention can be formed by electrospinning or electrospraying. By controlling the concentration of the deposition liquid, the deposition morphology, coverage and thickness, the fiber layer or particle layer can be constructed in a controllable manner, thereby providing an adjustable structural design space for different transparent thermal management application scenarios.
[0030] (5) Wide applicability: The transparent thermal management film provided by the present invention is applicable to fields such as transparent energy-saving windows, transparent automotive components and transparent building envelopes, and has good application prospects. Attached Figure Description
[0031] Figure 1 This is a schematic diagram of the overall structure of the transparent thermal management film of the present invention.
[0032] Figure 2 This is a comparison of the solar transmittance spectra of transparent composite matrix layers obtained by doping PDMS with different inorganic particles in Example 1.
[0033] Figure 3 This is a comparison of the solar transmittance spectra of the PDMS-ITO-PU spinning sample in Example 2 and the PDMS and PDMS-ITO samples in Example 1.
[0034] Figure 4 The transmission spectra of PDMS-ITO-PU spun samples obtained under different electrospinning parameters in Example 3 are compared: (a) receiving distance, (b) spinning voltage, (c) feed speed, (d) spinning time; (e) transmission spectra of the spun sample of Example 2 before electrospinning parameter optimization and the spun sample of Example 3 after electrospinning parameter optimization.
[0035] Figure 5 This is a photograph of the PDMS-ITO-PU spray sample from Example 4.
[0036] Figure 6 The solar transmittance spectrum comparison diagram of PDMS, PDMS-ITO, PDMS-ITO-PU spun samples and PDMS-ITO-PU sprayed samples in Example 4.
[0037] Figure 7 This is a comparison of the solar transmittance spectra of the PMMA-ATO transparent composite matrix layer with different ATO addition amounts in Example 5.
[0038] Figure reference numerals: 1-transparent composite matrix layer, 11-transparent polymer matrix, 12-near-infrared shielding particles, 2-electrostatically deposited micro / nano scattering layer, A-incident light direction. Detailed Implementation
[0039] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0040] The following embodiments primarily illustrate the invention using thermal management applications in automotive transparent components as an example, but the invention is not limited thereto. For those skilled in the art, applying the transparent thermal management film of this invention to transparent energy-saving windows, transparent building envelopes, or other transparent thermal management scenarios without departing from the concept of this invention falls within the scope of protection of this invention.
[0041] The structure of the transparent thermal management film in this invention is as follows: Figure 1 As shown, it includes a transparent composite substrate layer 1 and an electrostatically deposited micro / nano scattering layer 2 disposed on the surface of the transparent composite substrate layer 1 facing away from the incident light direction A; wherein, the transparent composite substrate layer 1 achieves pre-stage absorption of incident near-infrared radiation through the combination of a transparent polymer substrate 11 and near-infrared shielding particles 12; the electrostatically deposited micro / nano scattering layer 2 scatters and reflects the remaining near-infrared radiation transmitted through the transparent composite substrate layer 1 through the size effect of the micro / nano structure, thereby achieving synergistic thermal management of "pre-stage absorption - post-stage reflection".
[0042] In this invention, the transparent polymer matrix can be selected from polydimethylsiloxane (PDMS), polymethyl methacrylate (PMMA), or other transparent polymer materials; the near-infrared shielding particles can be selected from indium tin oxide (ITO), antimony-doped tin oxide (ATO), or other inorganic particles with near-infrared absorption, shielding, or modulation functions; the electrostatically deposited micro-nano scattering layer can be constructed by electrospinning or electrostatic spraying, and the material can be selected from polymer materials that can be electrostatically deposited, such as polyurethane (PU).
[0043] Unless otherwise specified, all materials and reagents used in the embodiments of the present invention are commercially available products.
[0044] The spectral properties of the transparent thermal management film can be characterized by a UV-Vis-NIR spectrophotometer, with a test wavelength range of 300-2500 nm; the visible light band is typically 380-780 nm, and the near-infrared band is typically 780-2500 nm.
[0045] Example 1
[0046] This embodiment relates to a transparent composite matrix layer doped with PDMS by different inorganic particles, and its preparation method includes the following steps:
[0047] (1) Preparation of PDMS matrix precursor: Weigh 10.0 g of polydimethylsiloxane (PDMS) prepolymer and place it in a clean beaker; then weigh 1.0 g of curing agent that is compatible with the PDMS prepolymer and add it to the PDMS prepolymer at a mass ratio of 10:1 to obtain the PDMS matrix precursor.
[0048] (2) Addition and dispersion of inorganic particles: 0.11 g of silicon dioxide (SiO2), titanium dioxide (TiO2), aluminum oxide (Al2O3), indium tin oxide (ITO) and antimony tin oxide (ATO) particles were weighed and added to different groups of PDMS matrix precursors (the amount of inorganic particles added was 1 wt% of the total mass of PDMS prepolymer and curing agent). After premixing with a glass rod, the mixture was stirred at 500 rpm for 15 min with a mechanical stirrer and then ultrasonically dispersed in an ultrasonic cleaner for 20 min to improve the dispersion uniformity of particles in the PDMS system. Subsequently, the mixture was placed in a vacuum degassing device for 15 min to remove bubbles from the system.
[0049] (3) Transparent composite matrix layer film formation and curing: PDMS matrix precursor and different composite precursors after degassing were respectively inverted onto the clean, horizontally placed glass substrate surface, and the film thickness was controlled to be about 500 μm using a film scraper; then the sample was placed in an 80 ℃ drying oven for 2 h to cure, and after cooling to room temperature, it was peeled off to obtain transparent composite matrix layer sample.
[0050] The above samples were named in sequence as: PDMS (without inorganic particles), PDMS-SiO2, PDMS-TiO2, PDMS-Al2O3, PDMS-ITO, and PDMS-ATO.
[0051] Figure 2 The images show a comparison of the solar transmittance spectra of transparent composite substrates obtained by doping PDMS with different inorganic particles. The test results show that the PDMS samples have high transmittance in the visible light band, but also high transmittance in the near-infrared band, making it difficult to effectively suppress solar radiation heat input. This indicates that relying solely on the transparent polymer matrix itself is insufficient to achieve effective transparent thermal management. Furthermore, the spectral modulation effects of different inorganic particles on the PDMS matrix vary significantly: PDMS-SiO2 and PDMS-Al2O3 samples have less impact on visible light transmittance compared to pure PDMS samples, but their transmittance in the near-infrared band shows an increasing trend; the PDMS-TiO2 sample shows a significant decrease in transmittance in the visible light band, which is detrimental to maintaining the transparency of the transparent thermal management film; both PDMS-ITO and PDMS-ATO samples show a decreasing trend in transmittance in the near-infrared band, with PDMS-ATO showing a certain increase in transmittance in some visible light bands, while PDMS-ITO shows a more significant decrease in transmittance in the near-infrared band.
[0052] The above results indicate that ITO and ATO are more suitable as near-infrared shielding particles in the transparent composite matrix layer of this invention. Considering their near-infrared blocking effect, transparency retention capability, and compatibility with subsequent processes, the PDMS-ITO transparent composite matrix layer is preferred. Compared with the pure PDMS sample, the introduction of ITO particles can perform pre-absorption of incident near-infrared radiation; however, its near-infrared blocking effect is still limited and insufficient to further enhance thermal management performance while maintaining high transparency, indicating that relying solely on a single absorption mechanism in the transparent composite matrix layer is still inadequate.
[0053] Example 2
[0054] This embodiment relates to a method for constructing an electrospun micro / nano structure layer on the surface of a transparent composite substrate layer facing away from the incident light direction, including the following steps:
[0055] (1) Selection of transparent composite matrix layer: The PDMS-ITO transparent composite matrix layer obtained in Example 1 was selected as the base layer. After the transparent composite matrix layer was cured into a film and peeled off, it was cut into a circular sample with a diameter of 5 cm and fixed on the surface of the electrospinning receiving device, with the side of the sample facing away from the incident light facing the spinning nozzle.
[0056] (2) Preparation of PU spinning solution: Weigh 1.75 g of polyurethane (PU) particles and add them to 8.25 g of N,N-dimethylformamide (DMF) / tetrahydrofuran (THF) mixed solvent (volume ratio 8:2) to prepare a PU spinning solution with a mass fraction of 17.5 wt%. Place the resulting mixture at room temperature and stir magnetically for 6 h to fully dissolve the PU and form a uniform and transparent spinning solution. Then let it stand to remove bubbles for later use.
[0057] (3) Construction of the back electrospun layer: The PU spinning solution was drawn into a syringe and connected to a metal needle; a single-needle electrospinning device was used to deposit the PU on the side of the PDMS-ITO transparent composite substrate layer facing away from the incident light. The process parameters used were: applied voltage 17 kV, feed rate 2 mL / h, receiving distance 15 cm, and spinning time 1.5 h. After spinning, the sample was placed at room temperature to allow the residual solvent to evaporate, resulting in a transparent thermal management film sample with a PU electrospun layer on the back, denoted as PDMS-ITO-PU.
[0058] Figure 3The solar transmittance spectra of the PDMS-ITO-PU sample prepared in this embodiment are compared with those of the PDMS and PDMS-ITO samples prepared in Example 1. The test results show that after introducing a PU electrospun layer on the surface of the PDMS-ITO transparent composite matrix layer facing away from the incident light direction, the transmittance of the sample in the near-infrared band further decreases. This indicates that the electrospun layer can scatter and reflect the remaining near-infrared radiation transmitted through the transparent composite matrix layer, thereby enhancing the sample's ability to block near-infrared radiation. However, it was also found that under the above spinning parameters, the introduction of the back electrospun layer leads to a decrease in the transmittance of the sample across the entire solar radiation band, especially significantly affecting the transmittance in the visible light band. This indicates that the thickness and coverage of the fiber layer formed under these conditions are still relatively high, which is not conducive to achieving better near-infrared control while maintaining transparency.
[0059] Therefore, this embodiment shows that constructing an electrospun micro / nano structure layer on the back of a transparent composite matrix layer can be one way to implement the present invention, but the specific spinning parameters still need to be further optimized in order to improve the balance between transparency and near-infrared blocking performance.
[0060] Example 3
[0061] This embodiment relates to a method for optimizing the electrospinning process parameters on the back side of a transparent composite matrix layer, including the following steps:
[0062] (1) Selection of transparent composite matrix layer: The PDMS-ITO transparent composite matrix layer selected in Example 1 is selected as the base layer, cut into a circular sample with a diameter of 5 cm, and fixed on the surface of the electrospinning receiving device, so that the side of the sample facing away from the incident light direction faces the spinning nozzle.
[0063] (2) Preparation of PU spinning solution: Weigh 2.00 g of PU particles and add them to 8.00 g of DMF / THF mixed solvent (volume ratio 8:2) to prepare a PU spinning solution with a mass fraction of 20 wt%. Place the resulting mixture at room temperature and stir magnetically for 6 h to fully dissolve the PU and form a homogeneous spinning solution; then let it stand to remove bubbles for later use.
[0064] (3) Control of electrospinning parameters: Under the premise of keeping the transparent composite matrix layer, spinning solution type and environmental conditions basically consistent, the applied voltage, advance speed, receiving distance and spinning time are adjusted respectively to optimize the construction parameters of the back electrospinning layer. Among them, the parameter optimization range may include: applied voltage 11-17 kV, advance speed 1-4 mL / h, receiving distance 10-20 cm, and spinning time 10-90 min.
[0065] The transparent thermal management film samples prepared by setting different receiving distances are respectively labeled as: PDMS-ITO-PU 5cm, PDMS-ITO-PU 10cm, and PDMS-ITO-PU 15cm.
[0066] The transparent thermal management film samples prepared by setting different spinning voltages are denoted as: PDMS-ITO-PU 11kv and PDMS-ITO-PU 17kv, respectively.
[0067] The transparent thermal management film samples prepared by setting different propulsion speeds were recorded as: PDMS-ITO-PU 2mL / h, PDMS-ITO-PU 3mL / h, and PDMS-ITO-PU 4mL / h.
[0068] Different spinning times were set, and the resulting transparent thermal management film samples were recorded as: PDMS-ITO-PU 5min and PDMS-ITO-PU 10min.
[0069] Figure 4 This is a comparison of the solar transmittance spectra of samples obtained under different electrospinning parameters in Example 3. Figure 4 Figures (a) to (d) show the effects of receiving distance, spinning voltage, feed speed, and spinning time on the transmission spectrum of the samples, respectively. The results indicate that the spectral modulation effect of the back fiber layer is closely related to the fiber characteristic size, deposition layer coverage, and overall thickness. Higher spinning solution concentration, shorter deposition time, moderate applied voltage, and suitable receiving distance are more conducive to forming a fiber layer with relatively large characteristic sizes and a thinner overall thickness on the back of the transparent composite matrix layer, thereby minimizing the adverse effects on visible light transmittance while reducing near-infrared transmittance. By adjusting the electrospinning process parameters, the balance between transparency and near-infrared blocking performance can be optimized to a certain extent.
[0070] Determination of optimal parameters: Based on the transmission spectrum test results of each group of samples, the optimal electrospinning parameters are as follows: applied voltage 11 kV, feed speed 2 mL / h, receiving distance 15 cm, spinning solution concentration 20 wt%, and spinning time 10 min. Electrospinning was performed on the surface of the PDMS-ITO transparent composite matrix layer facing away from the incident light direction under the above conditions to obtain the optimized sample, denoted as PDMS-ITO-PU spinning.
[0071] Figure 4 Results (e) show that after optimizing the spinning parameters, the transmittance of the PDMS-ITO-PU spun sample in the near-infrared band further decreased, while its visible light transmittance was improved compared with the sample under the initial spinning conditions in Example 2.
[0072] Example 4
[0073] This embodiment relates to a method for constructing an electrostatic sprayed micro / nano structure layer on the surface of a transparent composite substrate layer facing away from the incident light direction, and further compares the effects of the electrostatic sprayed layer and the electrospun layer on the spectral performance of the transparent thermal management film, including the following steps:
[0074] (1) Selection of transparent composite substrate layer: The PDMS-ITO transparent composite substrate layer obtained in Example 1 is selected as the base layer and cut into a circular sample with a diameter of 5 cm. It is fixed on the surface of the electrostatic deposition receiving device, with the side of the sample facing away from the incident light facing the nozzle.
[0075] (2) Preparation of PU spray solution: Weigh 0.75 g of PU particles and add them to 9.25 g of DMF / THF mixed solvent (volume ratio 8:2) to prepare a PU spray solution with a mass fraction of 7.5 wt%. Place the resulting mixture at room temperature and stir magnetically for 6 h to fully dissolve the PU and form a uniform spray solution; then let it stand to remove bubbles for later use.
[0076] (3) Construction of the back electrostatic spray layer: The PU spray liquid was drawn into a syringe and connected to a metal needle; an electrostatic deposition device was used to deposit the PU spray liquid on the surface of the PDMS-ITO transparent composite substrate layer facing away from the incident light direction. The process parameters used were: applied voltage 11 kV, advance speed 2 mL / h, receiving distance 15 cm, and deposition time 10 min. Under the above conditions, since the concentration of the deposition liquid was significantly lower than that of the electrospinning liquid in Example 3, the jet no longer formed continuous fibers, but instead transformed into a discrete droplet deposition state, thereby forming a discretely distributed micron- and / or nano-sized particle layer on the back of the transparent composite substrate layer, resulting in a transparent thermal management film with a PU electrostatic spray layer on the back, denoted as PDMS-ITO-PU spray. The sample photograph is shown below. Figure 5 As shown.
[0077] Figure 6 The solar transmittance spectra of the PDMS-ITO-PU spray sample prepared in Example 4 are compared with those of the PDMS, PDMS-ITO, and PDMS-ITO-PU spun samples prepared in Example 1 and Example 3, respectively. The test results show that the solar transmittance of the PDMS-ITO-PU spray sample is reduced by an average of 16.26% compared to the pure PDMS sample; by an average of 5.44% compared to the PDMS-ITO sample; and by an average of 0.5% compared to the PDMS-ITO-PU spun sample. The transmittance of the PDMS-ITO-PU spray sample in the visible light band is higher than that of the corresponding electrospun sample, while its transmittance in the near-infrared band is lower than that of the corresponding electrospun sample.
[0078] The above results show that in the bilayer structure of "transparent composite matrix layer + back electrostatic deposition micro-nano scattering layer" constructed in this invention, the back discrete particle layer formed by electrostatic spraying can more effectively scatter and reflect the remaining near-infrared radiation transmitted through the transparent composite matrix layer compared with the fiber layer formed by electrospinning, thereby achieving a better spectral modulation effect.
[0079] Example 5
[0080] This embodiment relates to a transparent composite matrix layer constructed using polymethyl methacrylate (PMMA) as a transparent polymer matrix and antimony tin oxide (ATO) as near-infrared shielding particles. The preparation method includes the following steps:
[0081] (1) Preparation of PMMA matrix precursor: Weigh 2.0 g of polymethyl methacrylate (PMMA) particles and add them to 8.0 g of DMF. Stir magnetically for 6 h at room temperature to fully dissolve the PMMA and form a uniform and transparent PMMA precursor solution.
[0082] (2) Preparation of samples with different ATO contents: 0.02 g, 0.10 g and 0.20 g of ATO particles were weighed and added to different groups of PMMA precursor solutions, corresponding to 1 wt%, 5 wt% and 10 wt% of PMMA mass, respectively. The resulting mixtures were treated by a combination of mechanical stirring and ultrasonic dispersion. The mechanical stirring speed was 500 rpm and the stirring time was 15 min, followed by ultrasonic dispersion for 20 min to improve the dispersion uniformity of ATO particles in the PMMA system. After dispersion, the mixtures were placed in a vacuum degassing device for 15 min to remove air bubbles from the system.
[0083] (3) Transparent composite matrix layer film formation and curing: PMMA matrix precursor and different PMMA / ATO precursors after degassing were respectively inverted onto the clean, horizontally placed glass substrate surface, and the film thickness was controlled to be about 500 μm using a film scraper; then the sample was placed in an 80 ℃ forced air drying oven to dry and cure for 2 h, and after cooling to room temperature, it was peeled off to obtain PMMA-ATO transparent composite matrix layer sample.
[0084] The above samples were labeled as follows: PMMA (without ATO), PMMA-ATO 1wt%, PMMA-ATO 5wt%, and PMMA-ATO 10wt%.
[0085] Figure 7This is a comparison of the solar transmittance spectra of the PMMA-ATO transparent composite matrix layer with different ATO addition amounts in Example 5. The test results show that after introducing ATO particles into the PMMA matrix, the transmittance of the sample decreased across the entire solar radiation spectrum, and the higher the ATO addition amount, the more significant the decrease in transmittance. The decrease in transmittance was particularly pronounced in the near-infrared band, indicating that the ATO particles have a certain absorption or shielding effect on near-infrared radiation. Further analysis shows that when the ATO addition amount is 1 wt%, the PMMA-ATO sample can still maintain a high visible light transmittance, basically meeting the requirements for transparent components. When the ATO addition amount increases to 5 wt% and 10 wt%, the transmittance of the sample in the visible light band decreases significantly. The visible light transmittance of the 10 wt% sample is lower than the general application requirements for transparent components, which is not conducive to the practical use of transparent thermal management films.
[0086] Therefore, this embodiment demonstrates that the PMMA system can also be used to construct the transparent composite matrix layer of the present invention, and the introduction of ATO particles can reduce near-infrared transmittance to a certain extent; however, compared with the aforementioned PDMS system, the PMMA-ATO system is more prone to causing a decrease in overall transmittance under higher doping conditions. Furthermore, solvent evaporation occurs in the PMMA precursor solution during film formation and drying, resulting in a certain deviation between the final film thickness and the preset coating thickness, which is detrimental to the stable control of sample thickness and spectral performance. Considering both transparency retention and near-infrared modulation effects, the present invention currently preferably uses the PDMS-ITO system as the transparent composite matrix layer.
Claims
1. A transparent thermal management film based on an electrostatically deposited micro / nano scattering layer, characterized in that, The transparent thermal management film includes a transparent composite substrate layer and an electrostatically deposited micro / nano scattering layer formed directly on the back surface of the transparent composite substrate layer by electrostatic deposition. The transparent composite substrate layer consists of a transparent polymer matrix and near-infrared shielding particles dispersed within the transparent polymer matrix. The near-infrared shielding particles are inorganic particles with near-infrared absorption, shielding, or modulation functions. The electrostatically deposited micro / nano scattering layer is a micro / nano particle layer formed by electrostatic spraying, composed of polymer materials and functional particles. The transparent polymer matrix is polydimethylsiloxane; the inorganic particles are indium tin oxide; the polymer material is a polymer material that can be electrostatically deposited, including one or more of polyurethane, polyamide, polyvinylidene fluoride, polyacrylonitrile, and polyvinyl alcohol; the functional particles are inorganic particles with spectral modulation functions, including one or more of indium tin oxide, antimony-doped tin oxide, titanium dioxide, silicon dioxide, and aluminum oxide.
2. A method for preparing a transparent thermal management film based on an electrostatically deposited micro / nano scattering layer as described in claim 1, comprising the following steps: (1) A transparent polymer matrix is provided, and near-infrared shielding particles are added thereto, and the matrix is mixed and dispersed to form a transparent composite matrix layer precursor; (2) The transparent composite matrix layer precursor is formed into a film and then cured or shaped to obtain a transparent composite matrix layer; (3) An electrostatically deposited micro-nano scattering layer is formed on the surface of the transparent composite substrate layer on the side opposite to the incident light direction by electrostatic deposition, thereby obtaining a transparent thermal management film.
3. The preparation method according to claim 2, characterized in that, In step (1), the near-infrared shielding particles are dispersed in the transparent polymer matrix by one or more of the following methods: mechanical stirring, ultrasonic dispersion, ball milling dispersion, or surface modification dispersion.
4. The preparation method according to claim 2, characterized in that, The film-forming method in step (2) is selected from one or more of the following: solution casting, scraping, casting, spin coating, spraying, molding, hot pressing, or in-situ curing.
5. The preparation method according to claim 2, characterized in that, The electrostatic deposition method described in step (3) is electrostatic spraying. The morphology, coverage and thickness of the electrostatically deposited micro-nano scattering layer are controlled by adjusting the concentration of the deposition liquid, the applied voltage, the propulsion speed, the receiving distance and the deposition time.
6. The application of a transparent thermal management film based on an electrostatically deposited micro / nano scattering layer as described in claim 1 in transparent energy-saving windows, transparent automotive components, or transparent building envelopes.
Citation Information
Patent Citations
High-sensitivity mechanical control intelligent window film and preparation method thereof
CN111522151A
Radiation refrigeration color nanofiber membrane with multi-layer structure and preparation method of radiation refrigeration color nanofiber membrane
CN117230580A
Nanofiber radiation refrigeration heat insulation film with bionic multilayer structure
CN121492437A